Can video- and sensor-based feedback by implementing a terrain-specific micro-pacing strategy improve performance in cross-country skiing? - Seeberg, T. M.; Kocbach, J.; Talsnes, R. K.; Meyer, F.; Losnegard, T.; Tjønnås, J.; Sandbakk, Ø. B.; Solli, G. S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Cross-country (XC) skiers employ a variable pacing pattern with higher metabolic rates and power production during uphill than flat and downhill sections. To improve performance, refining XC skiers` micro-pacing strategy through adjustments of speed in specific parts of flat and downhill terrain sections can be beneficial. Therefore, the aim of this study was to investigate performance-effects of video- and sensor-based feedback by implementing a terrain-specific micro-pacing strategy in XC skiing.